Application Of The Omnibus Law Concept In The Job Creation Law On The Environment And Economic Revival - Navis, Aulia Akbar; Hanif, Achmad Izzuddin; Iqbal, Muhammad; Siful, Siful (LEGAL BRIEF, 2024)
The Omnibus Law in the Job Creation Law was first passed by President Jokowi Dodo, intended to make regulations more effective and simplify so that they are right on target. The purpose of writing this article is to analyze the concept of Omnibus law and the application of the Job Creation Law to the environment and economic improvement. The research method used is normative juridical, with a statutory and conceptual approach with primary data sources, namely the 1945 Constitution and the Job Creation Law. Work, with secondary data, namely, books, research journals and so on. The results of the research on the rules in omnibus law are very beneficial for investors in Indonesia because they are too simple in the licensing stages, so they can increase the economic revival of the community but on the other hand also give rise to negative impacts on environmental sustainability because of this policy. Conclusion The Job Creation Law has a flawed legal basis, so it should need a review, both in the business industry licensing articles which are considered to be damaging and worrying about environmental sustainability, as well as articles which cause people's economic welfare to decline. As the decision of the panel of judges at the Constitutional Court stated that Omnibus Law still needs to be improved